An Exploratory of sentiment analysis on e-commerce business platform: Shopee Malaysia - Nor Hasliza Md. Saad,; Zulnaidi Yaacob,; Lee, Pei Sin (Penerbit Universiti Kebangsaan Malaysia, 2023)
The social media landscape creates opportunities for businesses to gain insights into public opinions about the brand, products and services issues discussed online. This research focuses on analysing public opinion on Twitter (currently rebranding to ‘X’) using Nvivo software. A qualitative technique was used to perform sentiment and content analyses on data gathered on 29 November 2021 concerning one of the top E-commerce business platforms in Malaysia, Shopee. In sentiment analysis, the cases of "Very Negative", "Moderately Negative", "Moderately Positive" and "Very Positive" were to be established. There are 3261 comments; 284 tweets have been coded as very negative, 122 as moderately negative, 412 as moderately positive, and 2443 as very positive. There are seven themes of the topic that emerged within the positive sentiment group: Customer satisfaction, customer service, delivery service, giveaway, promotion, seller satisfaction and socialising. Five themes for the negative sentiment group are identified: apps service, customer satisfaction, customer service, delivery service, and seller satisfaction. These findings will assist Shopee in determining what is effective and what is not. The findings add to the knowledge of e-commerce business platforms. It presents an overview of the public perspective for e-commerce businesses to understand the strengths and weaknesses of their services and react swiftly to customer demands.